EFFECTIVENESS BETWEEN PETIDINE AND TRAMADOL 50 MG TO OVERCOME SHIVERING IN PATIENTS SC WITH SPINAL ANESTHESIA - Leo Agustigno (PT. Anagata Sembagi Education, 2024)
Background: One of the anesthetic techniques that is often used in SC surgery is regional/spinal anesthesia. Shivering is the body's compensatory mechanism for hypothermia. The standard drugs used for shivering are petidine and tramadol. The aim was to compare the effectiveness of petidine with 50 mg tramadol to treat shivering in SC patients with spinal anesthesia at RSIA Lenggogeni Padang. Research Method: Quantitative method double blind randomized controlled clinical trial. The number of samples was 32, 16 people in the Petidine group and 16 people in the Tramadol group, using a purposive sampling technique. The instrument uses an observation sheet. Univariate and bivariate data analysis using the Mann Whitney U Test. Results of the study: Giving petidine showed that most of the respondents experienced grade 3 shivering (50.0%), and tramadol administration showed that most of the respondents experienced grade 4 shivering (37.5%). The mean value of the petidine group (16.66) was greater than the mean value of the 50 mg tramadol group (16.34). Conclusion: Giving petidine is more effective than giving tramadol 50 mg to treat shivering in SC patients with spinal anesthesia